Natuurlijke omgang? Een exegetisch-theologische verkenning van gelijkgeslachtelijke activiteit in vroegjoodse literatuur - Os, A. van den (2025)
This article examines early Jewish literature for its discussion on same-sex activities in the Bible. It will show that early Jewish authors do not restrict the prohibition of samesex activity to pederasty, but often reject same-sex activity because such behavior is unnatural. Other arguments derive from this principle. Early Jewish authors' arguments against same-sex activity is more similar to Hellenistic views than that of Old Testament texts. Although Paul deviates from the apologetical goals of early Jewish authors, their form of argumentation is also found in his writings. The overall conclusion is that Reformed theology should take note of the early Jewish positions and arguments in its discussion of the historical context of the Biblical speech on same-sex activities.